Effectiveness of Foreclosure Guarantees Due to Deafult on Crdit Agreements - Wida Nur Hanita; Dwi Mutiara Kartika Ningsih (International Journal of Law and Legal Ethics, 2022)
ABSTRACT The purpose of this study is to understand the basic provisions regarding the seizure of collateral goods and procedures or procedures for the seizure of property of the defendant. By using normative juridical research methods. The purpose of the seizure of collateral is to have a certain item that can be executed at a later date as payment of the defendant's debt. The conservatoir beslaag is a guarantee to enforce a civil judgment by freezing the defendant's property. Frozen cargo can later be used to enforce a court decision. The implementation of beslag protection begins with the determination of beslag protection by the District Court judges. The final stage of the implementation of sita jaminan is the preparation of a report of sita jaminan in accordance with the provisions of Article 197 (5) HIR, without the minutes of sita jaminan, the sita is considered void.